Iodine decrease in Caulerpa racemosa (Forsskal) J. Agardh in one-week storage duration. - Berones, Kathleen Amor R.; Yap-Dejeto, Leni G. (Tacloban City Kathleen Amor R. Berones, 2013)
Iodine is known to affect thyroid functions in humans. It is water-soluble and diffuses into the atmosphere under certain conditions. Caulerpa racemosa is a common dietary seaweed known to be a good source of iodine in the Philippines. However, there is no record of iodine concentration measurements in C. racemosa from Philippine waters. The expected decrease in iodine concentrations from harvested C. racemosa through time has never been measured. This study was thus conducted to calculate the daily changes in iodine level concentrations of C. racemosa stored for seven days. Titration analyses were done every twenty-four hours, with external factors such as the algal age and collection site kept constant. Post-storage conditions were adapted from how local vendors store leftover seaweed merchandise. Results revealed a decrease in iodine levels over time (P<0.001, alpha= 0.05, z=-8.110, r=-0.945). The initial concentration of iodine recovered was 196 ppm and dropped to 94.8 ppm on the seventh day. This is the first documentation of decrease in iodine concentration of C. racemosa over time. Iodine levels of C. racemosa were also compared with the recommended daily iodine intake.
Undergraduate thesis (B.S. Biology)--University of the Philippines, Tacloban